The Effects of Different Seed Rates on Yield and Economical Feasibility of Mustard (Brassica juncea) - Sarhadi, Wakil Ahmad; Naybkhil, Mir Zaman; Yousofzai, Wahida; Shams, Shamsurahan (Journal for Research in Applied Sciences and Biotechnology, 2024)
Rapeseed-mustard plant (Brassica juncea)” is any one of several plant species in the genera Brassica, Rhamphospermum and Sinapis in the family Brassicaceae (the mustard family). Mustard seed is used as a spice. Grinding and mixing the seeds with water, vinegar, or other liquids creates the yellow condiment known as prepared mustard. The seeds can also be pressed to make mustard oil, and the edible leaves can be eaten as mustard greens. Many vegetables are cultivated varieties of mustard plants; domestication may have begun 6,000 years ago. Mustard is a popular condiment, commonly it is a popular condiment made from the seeds of the mustard plant. It can be prepared using white/yellow mustard, brown mustard, or black mustard seeds mixed with liquids, salt, and other flavorings to create a paste or sauce. Mustard pairs well with meats, vegetables, and cheeses and is commonly used in sandwiches, hamburgers, and hot dogs. It is also used in dressings, glazes, sauces, and marinades around the world. The word "mustard" has origins in Latin and French, and archaeological evidence suggests mustard cultivation dates back to ancient civilizations like the Indus Valley. Mustard has a long history of culinary use, with the Romans likely being the first to experiment with mustard as a condiment. In France, Dijon became a renowned center for mustard making, and Dijon mustard is still highly regarded today. Mustard has various uses, such as a condiment, an ingredient in sauces and soups, and an emulsifier in dishes like Hollandaise sauce. The flavor and heat of mustard depend on the seed type and preparation method. Mustard offers nutritional benefits such as vitamins, minerals, and omega-3 fatty acids. Mustard plants is used for producing edible oil for human, oil-cake for feeding animals, sauce, spices, medicine and other purposes in Afghanistan. Mustard has a long history in Afghanistan and is mostly cultivated in the Northern provinces such as Baghlan, Kunduz, Thakkar, Samangan and etc. For the above-mentioned importance of Mustard, we decided to apply a research on seed rates to fine the desirable seed rate of mustard crop for Afghan Mustard growers. Seed rates are one of the important factors, which the suitable seed rates prevent from the economic loss of farmers. This research accomplished in the title of “The effects of different seed rates on yield and growth components of mustard (Brassica juncea)” The research was designed in a complete block design (RCBD) with three replications and five treatments. The data were collected from growth parameters such as plant height, number branches plant-1, number of leaves plant-1 as well as yield parameters such as number of pods plan-1, number of seeds plant-1, seed yield kg ha-1, dry matter kg ha-1 and biological yield kg ha-1. The collected data were analyzed using excel, OPSTAT online testing program, statistical tool for agricultural research (STAR). Based on the statistical analysis the significant differences were observed in all parameters at (P≥0.05. Least significant difference (LSD) was used to compare treatments. A positive correlation was also recognized between growth and yield parameters. Mostly treatment three (15 cm) space between rows performed high influence then the other treatments. We recommend much more research to find the best space between plant to plant and row to row. For the moment the farmers of Afghanistan can use the result of this research on their field for obtaining high yield from Mustard.